PERLAKUAN AKUNTANSI BIAYA PENGOLAHAN LIMBAH DALAM LAPORAN KEUANGAN (Studi Pada PT Amnor Shipyard – Batam ) - salesti, jayana (MEASUREMENT : Jurnal Program Studi Akuntansi, 2020)
The purpose of this study was to examine the data to analyze the data in the form ofcorporate financial statement in sewage treatment and evaluate whether the treatment of waste treatment costs are in accordance with applicable accounting standards. Company’s accounting treatment applied to the definition, measurement, recognition, presentation and disclosure. Judging from his testimony has not made a report specifically environmental costs. Recognition of costs alreadyrefer to the applicable Accounting Standart in accordance with the relevance of the cost of sewage treatment charged as elements of production cost in the current period.